Preparação e investigação das propriedades de filmes de polipirrol modificados com partículas metálicas magnéticas - Bergamaski, Franciele de Oliveira Freitas (Universidade Federal de São Carlos, 2005)
In this work, it was investigated the preparation and characterization of polypyrrole and nickel or cobalt doped popypyrrole. To prepare the doped samples, the monomer was polymerized in a solution containing the metal salt. The following preparation variables were investigated using the factorial design: synthesis charge, nickel salt concentration and synthesis potential or synthesis charge, synthesis potential and temperature for nickel and cobalt doped samples, respectvely. Besides, the surface response analysis was used to propose an empirical law to describe the amount of incorporated particles in the samples. The polymers were characterized using cyclic voltammetry and a new reduction current density peak was detected which was attributed to the reduction of the metallic particles. The quartz crystal microbalance allowed us to propose the existence of a redox pair between the polypyrrole and the nickel particles. The nickel doped film morphologies were characterized using the SEM technique and the results that the these parameters were affect by the presence of nickel salt during the sample preparation.
Keywords: Polímeros condutores; Polipirrol; Eletrodeposição; Níquel; Cobalto; Quimiometria; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::POLIMEROS E COLOIDES